2021
DOI: 10.47672/ajp.797
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Care, Perceived Social Support and Emotional Intelligence as Correlates of Psychological Health Among Caregivers of Mentally Ill Patients.

Abstract: Purpose: Psychological health has been reported as an important factor influencing individual’s various behaviors, activities, happiness and performance. This study examined burden of care, social support and emotional intelligence among caregivers of mentally ill patients as correlates of psychological health Materials and Methods: The research sample included two hundred (200) caregivers that were selected from the Federal Neuro-psychiatric hospital Yaba, Nigeia, using simple random sampling. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Similar aspects are described in a study about primary caregivers of relatives with dementia (taking into account the clinical differences between dementia and ABI but assessing the similarities of the caregivers’ situation): it was demonstrated that those who have higher levels of resilience and EI spend more time on self-care and leisure activities [ 30 ]. There is also a recommendation for family support groups to assist the caregivers of mentally ill patients because it was found that there was a significant inverse relationship between the burden of care and psychological health [ 31 ]. Furthermore, it is a need recognized for professional caregivers [ 32 ], a population that has been found to experience burnout, which acts as a stressor and reduces the quality of care provided.…”
Section: Discussionmentioning
confidence: 99%
“…Similar aspects are described in a study about primary caregivers of relatives with dementia (taking into account the clinical differences between dementia and ABI but assessing the similarities of the caregivers’ situation): it was demonstrated that those who have higher levels of resilience and EI spend more time on self-care and leisure activities [ 30 ]. There is also a recommendation for family support groups to assist the caregivers of mentally ill patients because it was found that there was a significant inverse relationship between the burden of care and psychological health [ 31 ]. Furthermore, it is a need recognized for professional caregivers [ 32 ], a population that has been found to experience burnout, which acts as a stressor and reduces the quality of care provided.…”
Section: Discussionmentioning
confidence: 99%